Pakistan Renal Data System (PKRDS): First Annual Report - Javed, Maryum; Khan, Azhar Ali; ,Akram, Mateen; Ahmad, Waqar (Pakistan Journal of Kidney Diseases, 2021)
Care of patients with chronic illnesses is a challenge. Several care management processes utilize different tools and protocols for maintaining a meaningful follow up and devise interventions. Clinical registries are one aspect of such management process and provide in depth look into the real-life presentations and management issues and needs of chronic diseases. Registries for kidney diseases are being maintained since long in the developed countries. Pakistan renal data system (PKRDS) is an effort in the same direction to maintain and acquire electronic data. The current review is the first report from the PKRDS.